Profiling Physics Pre-Service Teachers' Basic Teaching Skills Through Microteaching-Based Evaluation - Indhah Permatasari; Linda Dwi Astuti (Schrödinger: Journal of Physics Education, 2025)
Purpose of the study: This study aims to describe the profile of basic teaching skills of prospective physics teachers in a microteaching course. Methodology: This study uses a descriptive quantitative method was employed, using observation techniques. The observation technique was used to assess students' basic teaching skills during their microteaching practice. Main Findings: The results indicate that students’ basic teaching skills are generally good, although several aspects still require improvement. Skills in opening and closing lessons (87.04%), explaining material (89.3%), questioning (90.9%), reinforcement (82.6%), variation (88.5%), and classroom management and discipline (97.6%) were categorized as very good. Meanwhile, skills related to small group discussion (74.18%) and individualized instruction (63.89%) were classified as moderate and require further development. Novelty/Originality of this study: This study contributes to physics education pedagogy by providing empirical evidence on the specific teaching skill profile of prospective physics teachers, which can inform the design of microteaching programs oriented toward the unique characteristics of physics instruction. These findings highlight that, while most teaching skills are well developed, prospective physics teachers still need structured support in implementing collaborative learning and differentiation strategies to enhance the quality of physics teaching.